2014
DOI: 10.1111/lam.12223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sixListeriaspecies by real-time PCR assay

Abstract: Significance and Impact of the Study: The identification of species of Listeria from foods is important to monitor pathogenic strains and facilitates the implementation of control measures. This study shows the development and evaluation of a 5 0 exonuclease real-time PCR assay for the rapid identification of L. seeligeri, L. welshimeri, L. monocytogenes and L. ivanovii, L. grayi, L. innocua. The developed assay proved to be specific, rapid and reproducible and therefore could be implemented in busy specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…For rapid detection of L. monocytogenes in food matrices, lateral flow enzyme immunochromatography together with an immunomagnetic separation has been developed recently (Cho & Irudayaraj 2013). Molecular tools such as PCR, multiplex PCR and realtime PCR employing virulence-associated genes such as the mpl gene, prfA gene (Rossmanith et al 2006) and ssrA gene (O'grady et al 2008) have been found rapid, specific, reproducible and reliable (Portnoy et al 2002;Gianfranceschi et al 2013;Hage et al 2014;Khan et al 2014). Several multiplex PCR assays have been developed for simultaneous detection of various food-borne pathogens like Salmonella, Escherichia coli, Staphylococcus and also Listeria (Park et al 2006;Kawasaki et al 2009;Lee et al 2014).…”
Section: Diagnosismentioning
confidence: 98%
“…For rapid detection of L. monocytogenes in food matrices, lateral flow enzyme immunochromatography together with an immunomagnetic separation has been developed recently (Cho & Irudayaraj 2013). Molecular tools such as PCR, multiplex PCR and realtime PCR employing virulence-associated genes such as the mpl gene, prfA gene (Rossmanith et al 2006) and ssrA gene (O'grady et al 2008) have been found rapid, specific, reproducible and reliable (Portnoy et al 2002;Gianfranceschi et al 2013;Hage et al 2014;Khan et al 2014). Several multiplex PCR assays have been developed for simultaneous detection of various food-borne pathogens like Salmonella, Escherichia coli, Staphylococcus and also Listeria (Park et al 2006;Kawasaki et al 2009;Lee et al 2014).…”
Section: Diagnosismentioning
confidence: 98%
“…Furthermore, a novel 5′ exonuclease multiplex qPCR assay for the identification of six Listeria sp. including L. monocytogenes , L. seeligeri , L. ivanovii , L. welshimeri , L. grayi , and L. innocua was developed by Hage et al (2014) . In this study, two sets of triplex PCR were designed with one set identifying L. seeligeri , L. welshimeri , and L. monocytogenes and another set identifying L. ivanovii , L. grayi , and L. innocua .…”
Section: Molecular Detection Of Listeria Monocytogenesmentioning
confidence: 99%
“…Listeria spp. are small Gram+, non spore-forming, facultative anaerobic bacteria widely distributed in the environment [ 12 - 14 ]. The Listeria genus consists of 10 species: Listeria monocytogenes, Listeria ivanovii, Listeria fleischmannii, Listeria innocua, Listeria welshimeri, Listeria seeligeri , Listeria martini, Listeria rocourtiae, Listeria weihenstephanensis and Listeria grayi [ 15 - 20 ].…”
Section: Introductionmentioning
confidence: 99%